URBAN VENTILATION DI PERMUKIMAN BANTARAN SUNGAI Studi Kasus: Permukiman Bantaran Sungai Code, Kota Yogyakarta - , MOCHAMAD HILMY ([Yogyakarta] : Universitas Gadjah Mada, 2012)
It is presumed that the high density of buildings is one of the reasons for the raise in the temperature of urban areas. The increase in temperature is caused by the minimum air circulation in the city, affected by the hindrance created by the buildings and lack of open space. Urban ventilation is reputed to be a solution to suppress the imminence of urban heat island. The Code River, passing through the city of Yogyakarta, is potential for being used as a ventilation corridor of the urban areas. Disaster mitigation of the cold-lava flood has made it important to restructure the densely settlement on the Code Riverside area in order to establish a proper riverfront settlement. The wind flow at the Code Riverside area is influenced by the existence of the river and the river valley morphology, the level of density and the height of the buildings. FAR strategy is considered as a contributing answer to a satisfactory formation of ventilation. The ideal building is thin-shaped so as not to form a big wind shadow. The streets in the neighborhood of the densely settlement on the riversides become alley that allow air circulation throughout the area. A parametric study simulations conducted to obtain factors that affect the ventilation in the urban settlements along the river. River's border will support the ventilation optimally if it has a diagonal orientation to the prevailing wind. The optimal placement of flats to wind circulation in the surrounding environment can be achieved if it oriented into diagonal and stage and it given a distance of 15 to 20 m from the surrounding settlements. Alley at the riverfront settlement become into the circulation path of air entering the region. Structuring the environment oriented diagonal path to the prevailing wind can produce an optimal air circulation.